Paeonol attenuates retinopathy in streptozotocin-induced diabetes in rats by regulating the oxidative stress and polyol pathway - Adki, Kaveri M.; Kulkarni, Yogesh A. (Frontiers in Pharmacology, 2022)
Current research work was planned to study the effects of paeonol in the management of diabetic retinopathy. Diabetes was induced in male Sprague Dawley rats using Streptozotocin (55 mg/kg, i.p.). After four weeks, diabetic animals were treated with paeonol at a dose of 50, 100 and 200 mg/kg body weight daily for the next 4 weeks. At the end of treatment, retinal physiology was studied by recording an electroretinogram (ERG); biochemical parameters and oxidative stress were estimated. Histopathology of the retina was also carried out at the end of the study. ERG of paeonol treated animals showed significant improvement in a-wave amplitude, b-wave amplitude, a-wave latency and b-wave latency (p<0.001) at 15 cd.s/m2 when compared with diabetic control animals. Paeonol treatment (200 mg/kg) showed a significant decrease in the plasma glucose level (p<0.001) compared to diabetic control. Paeonol also significantly decreased lactate dehydrogenase, aldose reductase and sorbitol dehydrogenase levels as compared with diabetic control. Oxidative stress in the eye was significantly (p<0.05) reduced after paeonol treatment in diabetic rats. Histopathology showed a significant reduction (p<0.05) in retinal thickness after paeonol treatment. Results of the study indicate that Paeonol can be considered an effective management option for diabetic retinopathy.